Potensi Fraksi Etil Asetat Pelepah Nipah (Nypa fruticans. Wurmb) sebagai Antihiperglikemia pada Tikus yang Diinduksi Streptozotocin - Raharjo, Danang; Haryoto, Haryoto; Sujono, Tanti Azizah (FORIKES, 2025)
Diabetes mellitus remains a global health challenge. In Indonesia, diabetes ranks third as a killer disease after heart disease and cancer. Flavonoids as natural antioxidants have been proven effective in reducing the pathogenesis of diabetes and its complications. Nypa fruticans is one of the plants that has the potential as an antidiabetic with high flavonoid content. The purpose of this study was to explore the potential of the ethyl acetate fraction of nipah fronds as an antidiabetic, especially in reducing blood glucose levels, stimulating insulin secretion, improving pancreatic β-cells and increasing the number of pancreatic β-cells. This study was an experimental study conducted in-vivo with a streptozotocin (STZ)-induced diabetic rat model. The ethyl acetate fraction of nipah fronds with doses of 125, 250 and 500 mg/kgBW was administered to STZ-induced diabetic rats 65 mg/kgBW with glibenclamide 0.45 mg/kgBW as a comparison for 21 days with observed parameters including serum insulin levels and histopathology. The results showed that administration of the ethyl acetate fraction of nipah fronds at doses of 250 and 500 mg/kgBW caused a significant decrease (p<0.05) in blood glucose levels with a significant increase (p<0.05) in serum insulin levels compared to the negative control. In a histopathological study of the pancreas, the ethyl acetate fraction showed a regenerative effect on pancreatic β-cells by reducing the degree of insulitis and significantly increasing (p<0.05) the number of pancreatic β-cells in the islets of Langerhans compared to the negative control. Based on these results, it can be concluded that administration of the ethyl acetate fraction of nipah fronds exhibits antihyperglycemic activity by regenerating pancreatic β-cells and increasing the number of pancreatic β-cells, thereby increasing serum insulin levels.Keywords: Nypa fruticans Wurmb; antidiabetic; insulin secretion; insulitis; pancreatic β-cells ABSTRAK Diabetes mellitus masih menjadi tantangan kesehatan secara global. Di Indonesia, diabetes menduduki peringkat ketiga sebagai penyakit pembunuh setelah penyakit jantung dan kanker. Flavonoid sebagai antioksidan alami terbukti efektif dalam mengurangi patogenesis diabetes dan komplikasinya. Nypa fruticans merupakan salah satu tanaman yang berpotensi sebagai antidiabetes dengan kandungan tinggi flavonoid. Tujuan penelitian ini adalah mengeksplorasi potensi fraksi etil asetat pelepah nipah sebagai antidiabetes khususnya dalam menurunkan kadar glukosa darah, stimulasi sekresi insulin, perbaikan sel β-pankreas dan peningkatan jumlah sel β-pankreas. Penelitian ini merupakan studi eksperimental yang dilakukan secara in-vivo dengan model tikus diabetes yang diinduksi streptozotocin (STZ). Fraksi etil asetat pelepah nipah dengan dosis 125, 250 dan 500 mg/kgBB diberikan pada tikus diabetes yang diinduksi STZ 65 mg/kg BB dengan glibenclamide 0,45 mg/kgBB sebagai pembanding selama 21 hari dengan parameter yang diamati meliputi kadar insulin serum, dan histopatologi pankreas. Hasil penelitian menunjukkan bahwa pemberian fraksi etil asetat pelepah nipah dengan dosis 250 dan 500 mg/kgBB menyebabkan penurunan signifikan (p <0,05) kadar glukosa darah dengan peningkatan signifikan (p <0,05) kadar insulin serum jika dibandingkan dengan kontrol negatif. Dalam studi histopatologi pankreas fraksi etil asetat menunjukkan efek regenerasi sel β-pankreas dengan menurunkan derajat insulitis dan peningkatan secara signifikan (p <0,05) jumlah sel β-pankreas pulau Langerhans jika dibanding kontrol negatif. Berdasarkan hasil tersebut dapat disimpulkan bahwa pemberian fraksi etil asetat pelepah nipah menunjukkan aktivitas antihiperglikemik dengan meregenerasi sel-sel β-pankreas dan meningkatkan jumlah sel β-pankreas, sehingga meningkatkan kadar insulin serum.Kata kunci: Nypa fruticans Wurmb; antidiabetes; sekresi insulin; insulitis; sel β-pankreas